A mass-conserving algorithm for piston ring dynamical lubrication problems with cavitation. Issue 1 (8th January 2018) - He, Zhenpeng; Gong, Wenqin; Xie, Weisong; Zhang, Guichang; Hong, Zhenyu
Abstract : Purpose: Piston ring dynamic problem plays an important role in the lubricant characteristics of a reciprocating engine, which lead to engine wear and the increased consumption of lubricating oil. A cavitation analysis of the piston ring lubrication with two-dimensional Reynolds equation has rarely been reported owing to the complex working condition. The purpose of this study is to establish a precise model that can provide guidance for the design of the piston ring. Design/methodology/approach: In this paper, a cavitation model and its effect on the piston ring lubrication was studied in a simulation program based on the mass-conserving theory which is solved by means of the Newton–Raphson method. In this study, some models such as mixed lubrication, asperity contact, blow-by/blow-back flow and cavitation have been coupled with the lubrication model. Findings: The established model has been compared with the traditional model that deals with cavitation by using the Reynolds boundary condition algorithm. The cavitation zone, pressure distribution and density distribution between the piston ring and the cylinder have also been predicted. Studies of the changing trend for the pressure distribution and the cavitation zone at few typical crank angles have been listed to illustrate the cavitation changing rule. The analysis of the results indicates that the developed simulation model can adequately illustrate the lubrication problem of the piston ring system. All the analyses will provide guidance for the oil film rupture and the reformation process. Originality/value: A two-dimensional cavitation model based on the mass-conserving theory has been built. The cavitation-forming and -developing process for the piston ring–liner lubrication has been studied. Non-cavitation occurs in the vicinity of top dead center and bottom dead center. The non-cavitation period will be longer in the vicinity of 360° of crank angle. The density distribution in the cavitation zone can be obtained.